Internationalization of Domestic Crime in Iraqi Law (Crimes against Yazidi Women as a Case Study) - Al-Makhzoumy, Waleed (Journal of Legal Sciences, 2026)
The research addressed the phenomenon of countries resorting to internationalizing national crimes committed on their territory by transforming them into international crimes and the implications of this designation on them. It also addressed the position of the Iraqi legislator on this phenomenon in the texts of the Yazidi Survivors Law No. (8) of 2021, as it is considered the first legislation in which Iraq internationalized the crimes that occurred during the control of the ISIS terrorist organization over parts of Iraq. In it, the legislator described the crimes of this organization as international crimes and made it necessary for the perpetrators not to escape punishment by prohibiting amnesty and prohibiting the statute of limitations that would extinguish the punishment. On the one hand, it enshrined the right of the victims to redress the harm that befell them and to be compensated for the harm that befell them, in addition to their being subject to rehabilitation and social integration measures.